2013
DOI: 10.1177/1756283x13498540
|View full text |Cite
|
Sign up to set email alerts
|

Treating hepatocellular carcinoma progression following first-line sorafenib: therapeutic options and clinical observations

Abstract: Despite the established efficacy of sorafenib in advanced hepatocellular carcinoma (HCC), a significant number of sorafenib-treated patients experience disease progression. Current guidelines recommend either best supportive care or clinical trial enrollment for this population. As such, there remains an unmet need for tolerable, life-prolonging strategies in the second-line setting. New information regarding the molecular pathogenesis of resistance to antiangiogenic therapy and positive post-progression exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…Should alternative therapies with proven efficacy in the second-line setting not be available, the consensus statement recommends the continuation of sorafenib treatment after disease progression, which may be beneficial in slowing down tumor growth [60][61][62]. Evidence supporting this approach has recently come from a study measuring the size of metastatic lesions in patients with advanced HCC following their first radiologic progression of disease while receiving sorafenib [62].…”
Section: Treatment Beyond Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Should alternative therapies with proven efficacy in the second-line setting not be available, the consensus statement recommends the continuation of sorafenib treatment after disease progression, which may be beneficial in slowing down tumor growth [60][61][62]. Evidence supporting this approach has recently come from a study measuring the size of metastatic lesions in patients with advanced HCC following their first radiologic progression of disease while receiving sorafenib [62].…”
Section: Treatment Beyond Progressionmentioning
confidence: 99%
“…Expert opinion thus concludes that sorafenib may be continued after disease progression for patients with stable performance status, although there is currently no clear evidence from large studies supporting the effectiveness of this approach [60,61]. conclusion HCC is extremely heterogeneous in its nature and in most cases develops on a background of liver cirrhosis that has its own natural history.…”
Section: Treatment Beyond Progressionmentioning
confidence: 99%
“…However, treatment with agents targeting VEGF signaling often fails to yield sustained responses, because the majority of patients develop resistance (Schneider and Sledge, 2007;Bergers and Hanahan, 2008;Cortes-Funes, 2009;Grothey and Galanis, 2009;Mackey et al, 2012;He and Goldenberg, 2013;Vincent et al, 2015). This, together with the failure of these treatments to extend patients' survival, highlights the need for alternative antiangiogenic therapies based on fundamentally different principles and mechanisms.…”
Section: Pharmacological Targeting Of Pathologic Angiogenesismentioning
confidence: 99%
“…55,56 Another study revealed that HGF overexpression causes resistance to lenvatinib (a VEGFR inhibitor). This resistance is overcome by golvatinib (a c-Met inhibitor).…”
Section: C-met and Vegfmentioning
confidence: 99%